Patterns of mental health service use among perpetrators of domestic homicide: descriptive study of Domestic Homicide Reviews in England and Wales - Poppy MacInnes; Marilia A. Calcia; Michela Martinuzzi; Cora Griffin; Siân Oram; Louise M. Howard (BJPsych Bulletin)
Aims and method We used data from Domestic Homicide Reviews (DHRs) to describe the patterns of mental health service use by perpetrators of domestic homicide in England and Wales. In 186 DHR reports we compared the characteristics of perpetrators who accessed mental health services with those of perpetrators who did not. Separate analyses were conducted for perpetrators of intimate partner homicide (IPH) and family homicide.